Mar¡a Atkinson and the rise of Pentecostalism in the U.S.-Mexico borderlands - Avalos, Hector (The journal of religion & society, 2001)
María Atkinson is one of the most important women in the history of Pentecostalism in Mexico. She helped to establish the Mexican branch of the Church of God as well as Spanish-speaking churches in the American southwest. Yet, she remains a neglected figure among American historians of Pentecostalism. Some of this neglect is due to the fact that the study of Pentecostalism among Latinos is still in its infancy. Our study aims to correct this neglect, by providing a study of the life and work of María Atkinson within the socio-historical context of northern Mexico. Atkinson may be seen as an agent of an Americanization program encouraged by the Church of God and paralleled by American corporations. In particular, she became a conduit of Appalachian religious practices. In addition, this study explores the sociology behind Atkinson's meteoric rise and eventual eclipse in the Mexican branch of the Church of God.